Peculiarities of Public-Private Partnership - Sargsyan, Hayk (Journal of Sociology: Bulletin of Yerevan University, 2017)
Publicprivate partnership in all its manifestations has found distribution in the world – as a tool for creating a new infrastructure for organizing public works and services. The dynamics of this process in each country depends on the politics, on the desire to cooperate with business on the basis of economic and social consensus, the position of civil society. The variety of approaches to public-private partnerships, the uncertainty of this concept, are the result of the lack of a unified approach in international documents. Since there is no single approach to the term "public-private partnership", an attempt is made to reflect the most common expressive qualities of this cooperation, which characterizes various forms of interaction between public authorities and the private sector as PPPs.
Keywords: public-private partnership, mixed economy, indirect privatization, PPP projects, duties, risk sharing